Effects of Problem-Solving Activities on Korean Young Learners’ Critical Thinking and English Production - Park, Kyung-jin (English Teaching, 2022)
This study investigated the effects of complex problem-solving activities involving children's literature on students' critical thinking dispositions and English production. Thirty-one sixth-grade students were given lessons over a seven-week period. Various types of data were analyzed qualitatively, and the results of a critical thinking disposition test were analyzed quantitatively. Results were as follows: First, the critical thinking dispositions test revealed positive changes in open-mindedness, independence, objectivity, and inquisitiveness. The highest score was found for open-mindedness. The largest increase in score was for independence and objectivity. Second, changes in critical thinking dispositions enriched children's English production. Open-mindedness helped with spoken language production as it encouraged students to share their opinions freely. Independence was mainly expressed in writing form in which students could question and evaluate the text. Greater objectivity was applied to spoken and written language production as the subjects were able to recognize the importance of evidence. Inquisitiveness affected children's writing as it drove them to write down the results of their own research.